2016
DOI: 10.12659/msm.897011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Conventional Ultrasonography Combined with Contrast-Enhanced Ultrasonography in Thyroid Imaging Reporting and Data System (TI-RADS) 3 and 4 Thyroid Micronodules

Abstract: BackgroundThe present study was conducted to investigate the diagnostic performance of conventional ultrasonography (US) combined with contrast-enhanced ultrasonography (CEUS) in thyroid micronodules with thyroid imaging reporting and data system (TI-RADS) category 3 and 4.Material/MethodsThe features of conventional US and CEUS ion 102 case of thyroid micronodule samples, which were diagnosed based on pathological and clinical examination, were retrospectively analyzed. Logistic regression analysis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…A similar study was carried out by Xu et al in which 432 thyroid nodules were analyzed with CEUS and six suspicious features were pointed out as being specific in differentiating benign from malignant nodules: slow wash-in (p = 0.001), slow time to peak (p = 0.002), non-uniform enhancement (p = 0.023), irregular enhancement (p = 0.002), unclear enhancement boundary (p = 0.012) and no visible ring enhancement (p = 0.004) [34]. As in other studies, CEUS combined with TI-RADS showed better accuracy than any of the two alone, achieving a sensitivity of 85.66% and specificity of 83.33% [49,67].…”
Section: Quantitative Analysis Of Thyroid Nodules In Ceussupporting
confidence: 51%
“…A similar study was carried out by Xu et al in which 432 thyroid nodules were analyzed with CEUS and six suspicious features were pointed out as being specific in differentiating benign from malignant nodules: slow wash-in (p = 0.001), slow time to peak (p = 0.002), non-uniform enhancement (p = 0.023), irregular enhancement (p = 0.002), unclear enhancement boundary (p = 0.012) and no visible ring enhancement (p = 0.004) [34]. As in other studies, CEUS combined with TI-RADS showed better accuracy than any of the two alone, achieving a sensitivity of 85.66% and specificity of 83.33% [49,67].…”
Section: Quantitative Analysis Of Thyroid Nodules In Ceussupporting
confidence: 51%
“…Using ultrasonography (US) in thyroid nodule detection has raised the nodule prevalence to reach 67%. Seven to fifteen percent of thyroid nodules are malignant [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…With the increased use of ultrasound (US) in medical practice, there has been an increase in the number of detected thyroid nodules, which are detected in about 20–67% of the general population [ 1 3 ]. It is, therefore, important to establish a standard method to accurately assess thyroid nodules.…”
Section: Introductionmentioning
confidence: 99%